METABOLIC CHANGES WITH ATORVASTATIN IN TYPE 2 DIABETIC JORDANIAN PATIENTS - Khasawnah, Nadia (European Scientific Journal, ESJ, 2013)
ï»¿ï»¿Atorvastatin, potent lipid lowering agent, has beneficial effects in enhancing insulin sensitivity. Its role in improving liver enzymes is controversial. This study aimed to investigate the effects of atorvastatin in improving liver enzymes. Our study included 62 patients with diabetes type 2. They were assigned into two groups: experimental group of 33 patients who received atorvastatin treatment for 2 months and control group of 29 patients. Blood samples were obtained before and after the experiment. Lipid profile, glucose and liver function test profile were observed. The results showed that both cholesterol and triglycerides levels decreased significantly (p value 0.019 and 0.025 respectively). No significant changes in glucose level were observed (p value>0.05). Of liver enzyme profile, AST decreased significantly (p value 0.05). ALP, CKNAC, total proteins and total bilirubin did not show significant changes (p value >0.05). Conclusion: Atorvastatin treatment decreased cholesterol and triglycerides, and improved liver enzymes in diabetic type 2 patients.